El contrato-ley treinta años después: balance desde el Derecho interno y la protección internacional de inversiones - Garcés Gutiérrez, Miguel; Tovar Otero, Ignacio (Pontificia Universidad Católica del Perú, 2025)
The legal stability agreement (contrato-ley) was incorporated into the Peruvian legal system in the 1970s and subsequently consolidated at the statutory level through Article 1357 of the 1984 Civil Code. The 1993 Constitution later opted for its constitutionalization in response to a historical context marked by distrust toward state interventionism during the preceding decade. More than thirty years after that decision, this article examines whether the constitutionalization of the contrato-ley provided any genuine added value for foreign investors in terms of legal certainty, as compared to the preexisting statutory framework. The authors argue that such added value did exist, albeit with differentiated effects depending on the legal framework concerned. From the perspective of domestic law, constitutionalization had a limited impact, as the prior legal framework already precluded the modification of the contrato-ley and protected investors against the application of measures incompatible with the legal regime in force at the time of contracting. By contrast, in the field of international investment law, the impact was more tangible, as constitutionalization reduced the State’s ability to invoke the invalidity of the investment as a defense and more effectively constrained reliance on sovereign powers as a justification for contractual non-compliance.

El contrato-ley fue incorporado al ordenamiento jurídico peruano en la década de 1970 y consolidado legislativamente mediante el artículo 1357 del Código Civil de 1984. Posteriormente, la Constitución de 1993 optó por su constitucionalización como respuesta a un contexto histórico marcado por la desconfianza frente al intervencionismo estatal de la década anterior. A más de treinta años de dicha decisión, el presente artículo examina si la constitucionalización del contrato-ley aportó un verdadero valor agregado para el inversionista extranjero en términos de seguridad jurídica, en comparación con el régimen de rango legal preexistente. Los autores sostienen que dicho aporte sí existió, aunque con alcances diferenciados según el plano normativo. En el ámbito del Derecho interno, la constitucionalización tiene un alcance limitado, pues el marco normativo previo ya impedía la modificación del contrato-ley y protegía al inversionista frente a la aplicación de disposiciones incompatibles con el ordenamiento vigente al momento de la contratación. En cambio, en el plano del Derecho internacional de las inversiones, el impacto es más significativo, pues reduce la posibilidad de que el Estado alegue la invalidez de la inversión como mecanismo de defensa ante reclamos bajo tratado y limita de manera más efectiva la invocación de poderes soberanos como justificación para el incumplimiento contractual.
The contract-law thirty years later: an assessment from the perspective of domestic law and international investment protection
Keywords: Peruvian legal stability agreement; Constitution; Stabilization clause; Legitimate expectations; Contrato-ley; Constitución; Cláusula de estabilidad; Legítimas expectativas; https://purl.org/pe-repo/ocde/ford#5.05.01